Pengaruh Pasar Modal Global dan Perdagangan Internasional Terhadap Volatilitas Nilai Tukar Mata Uang Negara Asean dalam Perspektif Ekonomi Islam (Tahun 2018-2023) - Mulia Marta Sutrisno; Asriani Asriani; Muhammad Iqbal Fasa (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study is based on the international economic turmoil of ASEAN countries during the period 2018 - 2023 caused by the pandemic, the issue of the 2023 recession, and the internal turmoil of each country itself. This study analyzes the effect of global capital market variables and international trade variables on the exchange rate volatility of ASEAN countries from 2018 to 2023. The influence between the independent variables and the dependent variables is connected using the balance of payments theory. The study was analyzed using quantitative methods with secondary data from the ASEAN Statistical Yearbook. The analysis includes descriptive statistics, classical assumption tests, and panel data regression. The results of the study show that the global capital market has a significant negative effect, while international trade has a significant positive effect on exchange rate volatility. Together, all independent variables have a significant positive effect on the dependent variable, meaning that all independent variables have a significant effect both partially and simultaneously.